Practical research methods for librarians and information professionals - Beck, Susan E. (Neal-Schuman Publishers, 2008)
This book offers step-by-step guidance for using traditional research methods to help improve, validate, and ultimately advance the day-to-day work and purpose of libraries. Authors straight-forward and understandable approach show how different methodologies focus groups, usability tests, action research, transaction analysis, bibliometrics can be used to evaluate and enhance library functions, including: Reference interviews; Collection and resource evaluation; Programming; Workflow, and Web site design and usage and more. Each chapter outlines a particular methodology s process, including: selecting the research topic, formulating questions, defining the population, gathering data, interpreting evidence, and telling the story. Specific advice for navigating legal and ethical concerns, avoiding incorrect inferences, overcoming communication obstacles, and working with institutional review boards is also included